Quantitative Study of Volumetric Changes of Cerebellum in Male Adult Rat Following Lithium Administration - Heidari, Zahra (Kowsar, 2012)
BACKGROUND: Lithium is a drug for treatment of bipolar disorder by correcting mania and reducing depressive mood swings. OBJECTIVES: In this study, effects of Lithium on volumetric parameters of cerebellum were investigated using stereological methods. MATERIALS AND METHODS: In this experimental study, 20 sexually mature wistar male rats were selected and divided in two groups randomly (n = 10). Administration and control groups received continuously 0.1 percent Lithium carbonate solution and distilled water respectively with drinking water during a period of 12 weeks. Rat’s cerebellum excised and fixed in modified Lillie’s solution. Then tissues were dehydrated, cleared, and embedded in paraplast in random orientation, and exhaustively sectioned. Ten to twelve sections of ~ 5μm were sampled and stained from each cerebellum by systematic uniform random sampling. The whole section image projected on the table, and using Cavalier’s principle point-counting was employed to estimate the volumetric parameters. Data analyzed by nonparametric statistical test of Mann-Whitney, and differences between groups less than 0.05 considered significant. RESULTS: There were no significant difference in terms of total volume but gray matter volume of cerebellum increased and white matter decreased in administration group significantly (P < 0.05). CONCLUSIONS: Administration of 0.1% Lithium carbonate for a period of 12 weeks can affect cerebellar gray and white matters in rat.